Analysis of The Factor That Influence The Incidence of CED In Pregnant Women at Turi Health Center Lamongan Regency: Analysis of The Factor That Influence The Incidence of CED In Pregnant Women at Turi Health Center Lamongan Regency - Devy Putri Nursanti (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
The high incidence of CED in pregnant women at Puskesmas Turi is caused by maternal parity which has an impact on the incidence of prolonged labor and delivery bleeding. The purpose of the study was to analyze the factors of parity, pregnancy spacing, and work status on the incidence of CED in pregnant women in Turi Health Center. The study uses a quantitative approach with cross sectional study design. The total population of 77 pregnant women and taken as many as 64 people with simple random sampling technique. Analysis using chi square and phi. The results showed that pregnant women with multipara parity were at risk of experiencing CED from the statistical test results, namely p-value of 0.012, α = 0.05, p<α, then H1 was accepted and H0 was rejected. This showed the influence between Parity and the incidence of CED in pregnant women at the Turi Health Center. Pregnant women with a pregnancy interval <lt;2 years until 10 years are at risk of experiencing CED from the statistical test results, the p-value of 0.044, α = 0.05, p <α, then H1 is accepted and H0 is rejected, this shows the influence between Distance between Pregnancy and CED events for pregnant women in Turi Health Center. In addition, pregnant women who do not work are at risk of experiencing CEDs from the statistical test results, namely p-value of 0.025, α = 0.05, p <α, then H1 is accepted and H0 is rejected, this shows the influence between occupational status and the incidence of CEDs in the mother pregnant at Turi Health Center. The conclusion of this research is the need for health promotion efforts on the importance of planning the number of children and how to regulate the distance of pregnancy and efforts to increase income for mothers who do not work.